2011
DOI: 10.1371/journal.pone.0025698
|View full text |Cite
|
Sign up to set email alerts
|

How Do Patients Who Fail First-Line TB Treatment but Who Are Not Placed on an MDR-TB Regimen Fare in South India?

Abstract: SettingSeven districts in Andhra Pradesh, South IndiaObjectivesTo a) determine treatment outcomes of patients who fail first line anti-TB treatment and are not placed on an multi-drug resistant TB (MDR-TB) regimen, and b) relate the treatment outcomes to culture and drug susceptibility patterns (C&DST).DesignRetrospective cohort study using routine programme data and Mycobacterium TB Culture C&DST between July 2008 and December 2009.ResultsThere were 202 individuals given a re-treatment regimen and included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…This study also revealed that INH resistance is seen in 39% cases in this geographical area. According to Burugina Nagaraja et al .,[ 6 ] treatment outcomes of patients who fail a first-line anti-TB therapy and who are not placed on an MDR-TB regimen are unacceptably poor. [ 6 ] Hence, there is a need to start MDR-TB regimen in cases of drug resistant TB other than MDR.…”
Section: Discussionmentioning
confidence: 99%
“…This study also revealed that INH resistance is seen in 39% cases in this geographical area. According to Burugina Nagaraja et al .,[ 6 ] treatment outcomes of patients who fail a first-line anti-TB therapy and who are not placed on an MDR-TB regimen are unacceptably poor. [ 6 ] Hence, there is a need to start MDR-TB regimen in cases of drug resistant TB other than MDR.…”
Section: Discussionmentioning
confidence: 99%
“…Unfinished first-line TB treatment has emerged as a large proportion of MDR-TB incidences, consisting of failure, default and relapse of TB treatment [3,5]. Management of TB therapy on non-directly observed treatments (DOTs) at health facilities [3,6], the lack of a gold standard of drug-susceptibility facilities for diagnosis [7,8] and poor TB patient access to medication [5,[8][9][10] are the main determinant factors for MDR-TB control, which is more complex in an under-resourced country setting.…”
Section: Background Rationalementioning
confidence: 99%
“…With the long course of treatment and side effects, most people in the affected regions stopped taking medication when they started feeling well without completing the required dosage (Hedt et al 2011 ; Rahman et al 2014 ) . This behaviour resulted in development of bacteria that were able to withstand the drugs used for treatment (Almeida Da Silva and Palomino 2011 ; Chadha et al 2011 ; Daniel and Osman 2011 ; Hoek et al 2009 ; Nagaraja et al, 2011 ; States et al 2006 ; Tang et al 2013 ; WHO, 2010 ) . By cutting short the course of treatment, it meant that there was reduced drug pressure on the disease causing bacteria, which were then able to survive the treatment, and became more resilient.…”
Section: Disease Impact and Case Scenariosmentioning
confidence: 99%